From service quality to loyalty and economic behaviour in food delivery platforms - Khaeri; Siti Aisyah Putri Maharani Simamora; Azura Zeyna Rohman; Indra Irjani Dewijanti (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2025)
This study examines how service quality shapes user perceptions and behavioural outcomes in online food delivery platforms by analysing the interrelationships among service quality, perceived value, customer satisfaction, customer loyalty, and economic behaviour. Using a structural equation modelling partial least squares approach, data were collected from 320 active users of major delivery applications in Indonesia. The findings demonstrate that service quality significantly enhances both perceived value and satisfaction, which subsequently strengthen loyalty. Customer loyalty is further shown to influence economic behaviour reflected in repeat usage and higher spending intentions. Mediation analyses reveal that perceived value and satisfaction operate as key psychological mechanisms transmitting the influence of service quality toward loyalty. These results contribute to foodservice business research by clarifying cognitive and affective pathways within the digital delivery context and offering actionable managerial implications for platform providers seeking to cultivate sustainable user engagement